4-in-1 Quadricepsplasty for Habitual and Fixed Lateral Patellar Dislocation in Children. Issue 4 (23rd April 2023) - Parikh, Shital N.; Lopreiato, Nicholas; Veerkamp, Matthew
Abstract : Background: Habitual and fixed patellar dislocations represent extreme forms of patellar instability and can lead to significant functional loss. The underlying complex pathoanatomy of a laterally positioned and shortened extensor mechanism poses challenges in its management. The purpose of our study was to evaluate the anatomic risk factors and outcomes of a 4-in-1 quadricepsplasty (wide lateral releases, Insall proximal tube realignment, Roux-Goldthwait patellar tendon hemi-transfer, and step-wise quadriceps lengthening) for stabilization of habitual and fixed patellar dislocation. Methods: In a retrospective study, all patients with habitual and fixed patellar dislocation who underwent 4-in-1 quadricepsplasty and had a minimum 2-year follow-up were identified. Preoperative magnetic resonance imagings were evaluated for the presence of anatomic risk factors. As a prospective part of the study, patient-reported outcomes were collected using validated instruments including Pedi-IKDC, HSS-Pedi FABS activity score, BPII 2.0 score, Kujala score, and KOOS score. Results: Seventeen knees (12 patients) formed the study cohort. Twelve knees had habitual dislocation (9 in extension and 4 in flexion) and 5 had fixed dislocation. Mean age was 9 years. 6/17 (35.3%) knees were associated with syndromes. On magnetic resonance imaging, trochlear dysplasia was the most common anatomic risk factor present in 15/17 (88.2%) knees. 13/17 (76%) knees had presence of 2 or more risk factors. At the mean follow-up of 43.3 months, the mean Pedi-IKDC score was 88.1, the HSS-Pedi FABS activity score was 15.6, the BPII 2.0 score was 78.2, the Kujala score was 90, KOOS score was 93.9, and overall patient satisfaction score was 83.3. For complications, 3/17 knees (17.6%) had recurrent patellar instability, 1 knee had postoperative stiffness that required manipulation under anesthesia and 1 knee had a superficial wound infection. Conclusions: Most patients with habitual and fixed patellar dislocation present during the first decade of life. There are several underlying anatomic risk factors, the most common being trochlear dysplasia and patellar tilt. The 4-in-1 quadricepsplasty technique provides reliable patellar stabilization, satisfactory clinical results, and acceptable patient-reported outcomes at a minimum 2-year follow-up, with a 17.6% redislocation rate. Level of Evidence: Level IV.